A decomposition method for approximating Pareto frontier in Multiobjective Integer Linear Problems - Bushenkov, Vladimir (2012)
A new iterative method that approximates the Pareto frontier in MOILP by pairs of interior and exterior estimates which converge each other during the iterations. These estimates are obtained by combining Convex Edgeworth-Pareto Hulls constructed for a number of subsets into which the original Feasible Criteria Set is decomposed.